Metabolomics in Prenatal Medicine: A Review - Monni, Giovanni; Atzori, Luigi; Corda, Valentina; Dessolis, Francesca; Iuculano, Ambra; Hurt, K. Joseph; Murgia, Federica (Frontiers in Medicine, 2021)
Pregnancy represent a complicated and insidious state, with various aspects to consider including the well-being of the mother and child. Developing better non-invasive tests that cover a broader range of disorders with lower false positive rates is a fundamental necessity in the prenatal medicine field, and in this sense, the applications of metabolomics could be extremely useful. Metabolomics measures and analyses the products of cellular biochemistry. As a biomarker discovery tool, the integrated holistic approach of metabolomics can yield new diagnostic or therapeutic approaches.. In this review, we identify and summarize prenatal metabolomics studies and identify themes and controversies. We conducted a comprehensive search of PubMed and Google Scholar for all publications through January 2020 using combinations of these keywords: nuclear magnetic resonance, mass spectrometry, metabolic profiling, prenatal diagnosis, pregnancy, chromosomal or aneuploidy, preeclampsia, fetal growth restriction, preterm labor, and congenital defect. Metabolite detection with high throughput systems aided by advanced bioinformatics and network analysis allowed the identification of new potential prenatal biomarkers and therapeutic targets. We took into consideration the scientific papers issued between the years 2000-2020, thus observing that the larger number of them were mainly published in the last 10 years. Initial small metabolomics studies in perinatology suggest that previously unidentified biochemical pathways and predictive biomarkers may be clinically useful. Although the scientific community is considering metabolomics with increasing attention for the study of prenatal medicine as well, more in-depth studies would be useful in order to advance toward the clinic world as the obtained results appear to be still preliminary. Employing metabolomics approaches to understand fetal and perinatal pathophysiology needs further research with larger sample sizes and rigorous testing of pilot studies using various omics and traditional hypothesis-driven experimental approaches.